2013
DOI: 10.1021/jp407176j
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Room-Temperature Ionic Liquids on CO2 Separation by a Cu-BTC Metal–Organic Framework

Abstract: We report a molecular simulation study aimed to ascertain the effect exerted in gas adsorption when room-temperature ionic liquids (RTILs) are added into the pores of the Cu-BTC metal-organic framework (MOF). Carbon dioxide, methane, nitrogen, and their mixtures are studied. We take into account the influence of the type of anion and the relative amount of RTILs used. It is observed that the presence of RTILs in the MOF pores enhances significantly CO2 adsorption at low pressures, whereas methane and nitrogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
87
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(95 citation statements)
references
References 62 publications
5
87
0
Order By: Relevance
“…To understand the effect of different types of ILs on the separation performances of IL-MOF systems, ILs with the same cations but different anions were studied. [18][19] However, among the researches considering IL-MOF couples, there are limited numbers of studies focusing on the elucidation of reasons for better gas selectivities obtained by the incorporation of ILs into the pores of MOFs. Xue et al 20 4 ] with different loadings into the cages of Cu-BTC and obtained improvements in CH 4 /H 2 , N 2 /H 2 , and CH 4 /N 2 selectivities as a consequence of the interactions between IL and MOF.…”
Section: Introductionmentioning
confidence: 99%
“…To understand the effect of different types of ILs on the separation performances of IL-MOF systems, ILs with the same cations but different anions were studied. [18][19] However, among the researches considering IL-MOF couples, there are limited numbers of studies focusing on the elucidation of reasons for better gas selectivities obtained by the incorporation of ILs into the pores of MOFs. Xue et al 20 4 ] with different loadings into the cages of Cu-BTC and obtained improvements in CH 4 /H 2 , N 2 /H 2 , and CH 4 /N 2 selectivities as a consequence of the interactions between IL and MOF.…”
Section: Introductionmentioning
confidence: 99%
“…Metal-organic framework materials (MOFs), which consist of metal ions with bridging organic linkers and have two-or three-dimensional structures (Rowsell and Yaghi 2004;Davydovskaya et al 2014;Khan and Jhung 2015), have been a hot topic with a wide variety of compositions and reported by many journals in all kinds of application such as removal of toxic gas and hazardous organics (Barea et al 2014;DeCoste and Peterson 2014;Hasan and Jhung 2015), separation of methylene blue (Lin et al 2014;Wang et al 2014), sensing device and absorption of gas such as CO 2 and methane (Vicent-Luna et al 2013;Lei et al 2014;Sun et al 2014;Kim et al 2015). Very recently, MOFs have also shown activity in bacteria restraint derived from metal ions.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies regarding gas adsorption properties of MOF-supported ILs have been mainly computational simulations [141][142][143][144]. A composite of [BMIM][PF 6 ] IL supported on IRMOF-1 was investigated for CO 2 capture by molecular computation by Chen and coworkers [141].…”
Section: Computational Studiesmentioning
confidence: 99%
“…Vicent-Luna and co-workers [143] reported a molecular simulation study aimed to determine the effect over gas adsorption of the addition of RTILs into Cu-BTC MOF pores. It was observed that the presence of RTILs in the MOF pores enhanced significantly CO 2 adsorption at low pressures, whereas CH 4 and N 2 adsorption remains unaffected.…”
Section: Computational Studiesmentioning
confidence: 99%